الشخصية الكارزمية لدى معلمات رياض الأطفال( بناء وتطبيق) (Journal of the College of Basic Education, 2024)
1- The charismatic personality of kindergarten teachers.2- Identify the charismatic personality of kindergarten teachers according to the variable of specialization.To achieve the objectives of the current research, the researcher has chosen the research community from kindergarten teachers in the city of Baghdad with its sides Karkh and Rusafa, and the research sample has reached (400) parameters has been preparing a scale (charismatic personality), which reached the number of paragraphs (30) paragraph and after extracting the psychometric properties of honesty and stability using statistical media (arithmetic mean, standard deviation, T-test to one sample, T-test to two independent samples, Pearson's correlation coefficient, alpha Krum Bach coefficient, analysis of single variance, and the Scheffe equation For dimensional comparisons), the final version of the two scales was come up with and applied to the basic sample and after processing the data statistically the researcher reached the following1 Kindergarten teachers have a good charismatic personality.2 There are no differences between kindergarten teachers in the charismatic personality according to their specialization (kindergarten, another specialty).